Understanding of Accounting and Gender on Financial Literation Levels - Muhamad Iskhak (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to analyze the effect of understanding accounting and gender on the level of financial literacy of postgraduate students in the economic education program at Surabaya State University. This research uses a quantitative approach. The study showed that the level of financial literacy of postgraduate students of economic education courses at UNESA was 19.7% at the high level, 32.4% at the moderate level, and 47.9% at the low level. The level of financial literacy shows an average of 60.49, and the meaning is moderate. Accounting understanding shows an average of 70.28, and it means that the level of accounting understanding is moderate. The participation rate was 43.7% male and 56.3% female. The level of financial literacy of students in the female gender group was higher than male, female by 62.00 (62.00> 60) which means moderate, and male by 58.55 (58.55 <60) which means low. Based on data analysis, it can be concluded that accounting understanding has a significant effect on the level of financial literacy of postgraduate students in economic education programs at UNESA. Meanwhile, gender has no significant effect.